A methods engineering study on the Peninsula Manila - Guanio, Terence (College of Engineering, 2001)
Hotel service demands constant evaluation and improvement of methods and procedures. In this report the group was lucky to have become part of the quest of the Peninsula Manila in further improving its service through conducting a work study on two of its very vital departments, the Housekeeping department and the Lobby Restaurant. In the housekeeping department, the group chose to focus on evaluating the current 14 room quota for the room attendants because focusing on this topic would also bring about the accomplishment of the objectives set by the management at the beginning of the project. These specific objectives are : 1) Understand the job of the room attendant, 2) Identify inefficient methods and 3) set basis for productivity targets (obtain standard times). The group limited the scope of its study to standard rooms and the data obtained was only from the 7 am to 3 pm shift. In order to properly evaluate whether the 14 room quota was appropriate, the group first observed the job on cleaning the standard rooms. The group then used work sampling to be able to understand the components of the room attendant's work. This data was also used to obtain the standard time of cleaning one credit rooms, rooms which were considered as part of the 14 room quota. The group also used time study but this data was not used since computations proved that the sample size required to obtain an accurate standard time was too large for such a study to be carried out. With data from work sampling, the group was able to obtain a standard time for cleaning one credit rooms, 29.07 mins. With this standard time and other data from work sampling, the group was able to prove that the 14 room quota for the room attendants was too steep. The group proposed a new quota of 12 rooms. The group also investigated the current standards and procedures of the housekeeping department and identified possible areas for improvement. The same three objectives of 1.) Understanding the work 2) Identifying inefficient methods and 3) Developing standards for setting productivity targets were the main goals, which the management wanted to achieve in the study of the Lobby restaurant. Unfortunately with time and other constraints, the group was only able to conduct initial observations of the lobby service and to propose certain procedures and methods which could improve the current speed of the lobby restaurant service. The group tried to obtain the lead times between orders using a direct time study approach but the group's adviser recommended that the data obtained not be used due to the variability of the times obtained. The group focused on understanding the current procedures used by the Lobby restaurant and gave certain recommendations as how to improve the speed of the service.